2018
DOI: 10.1021/acs.jmedchem.8b00360
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Aminopiperidine Indoles That Activate the Guanine Nucleotide Exchange Factor SOS1 and Modulate RAS Signaling

Abstract: Deregulated RAS activity, often the result of mutation, is implicated in approximately 30% of all human cancers. Despite this statistic, no clinically successful treatment for RAS-driven tumors has yet been developed. One approach for modulating RAS activity is to target and affect the activity of proteins that interact with RAS, such as the guanine nucleotide exchange factor (GEF) son of sevenless homologue 1 (SOS1). Here, we report on structure-activity relationships (SAR) in an indole series of compounds. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 39 publications
6
48
0
Order By: Relevance
“…Rasarfin inhibits Ras, ARF6, and cell proliferation in cancer cells. Because Ras proteins are key regulators of normal cell proliferation and survival, inhibitors of this small G protein have been developed for the treatment of cancers [46][47][48] . We, therefore, assessed Rasarfin's effects on cancer cells viability and proliferation.…”
Section: Sar Studies On Rasarfin Identify Functionally Selective Analogsmentioning
confidence: 99%
“…Rasarfin inhibits Ras, ARF6, and cell proliferation in cancer cells. Because Ras proteins are key regulators of normal cell proliferation and survival, inhibitors of this small G protein have been developed for the treatment of cancers [46][47][48] . We, therefore, assessed Rasarfin's effects on cancer cells viability and proliferation.…”
Section: Sar Studies On Rasarfin Identify Functionally Selective Analogsmentioning
confidence: 99%
“…The ability of these compounds to affect SOS1-mediated nucleotide exchange was assessed by using a high-throughput nucleotide exchange assay (Burns et al, 2014Abbott et al, 2018). Data analysis showed that compound 34 (Figure 7) had an EM50 (in vitro compound potency was defined as the half maximal effective concentration .)…”
Section: Inhibition Of Sos-mediated Activationmentioning
confidence: 99%
“…For suppressing RAS-dependent signaling, several distinct series of small molecule activators that bind to a hydrophobic pocket in SOS1 in a RAS-SOS1-RAS ternary complex were discovered. Some of these binders activated the SOS1-mediated nucleotide exchange, resulting in reduced RAS signaling through negative feedback on SOS1 [25,26,27]. Most recently, the inhibitor of SOS1 was reported [28].…”
Section: Gef Structures and Mechanisms Of Small Gtpase Activationmentioning
confidence: 99%